Preparation of single chain nanoparticles via photoinduced radical coupling process - Dashan, Irem; Balta, Demet Karaca; Temel, Binnur Aydogan; Temel, Gokhan (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
This contribution introduces a straightforward method for preparing well-defined polymeric nanoparticles using radical coupling process of ketyl moieties resulted from triplet excitation of pendant benzophenone groups. In the first step, poly(styrene-co-chloromethylstyrene) is synthesized by thermally initiated controlled radical co-polymerization technique and subsequently, pendant chloride groups undergo post-modification with 4-hydroxybenzophenone. Achieved well-defined side-chain benzophenone containing copolymers generate ketyl radicals in the presence of excess hydrogen donor molecule upon UV-light irradiation and intramolecularly crosslinked nanoparticles are formed by radical coupling process in dilute regime. Resulting single chain nanoparticles and intermediates are characterized by H-1 NMR, gel permeation chromatography, differential scanning calorimetry, UV-Vis spectrometry and electron microscopy techniques.
Keywords: Polymeric nanoparticles; Single chain folding; Photoinduced ketyl coupling; Controlled radical polymerization; PHOTOINITIATOR; COPOLYMERS; ROUTE; LIGHT; BLOCK; ATRP; UV; Polymer Science